(2*7x)+(14+2x)*15=606

Simple and best practice solution for (2*7x)+(14+2x)*15=606 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2*7x)+(14+2x)*15=606 equation:


Simplifying
(2 * 7x) + (14 + 2x) * 15 = 606

Multiply 2 * 7
(14x) + (14 + 2x) * 15 = 606

Reorder the terms for easier multiplication:
(14x) + 15(14 + 2x) = 606
(14x) + (14 * 15 + 2x * 15) = 606
(14x) + (210 + 30x) = 606

Reorder the terms:
210 + (14x) + 30x = 606

Combine like terms: (14x) + 30x = 44x
210 + 44x = 606

Solving
210 + 44x = 606

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-210' to each side of the equation.
210 + -210 + 44x = 606 + -210

Combine like terms: 210 + -210 = 0
0 + 44x = 606 + -210
44x = 606 + -210

Combine like terms: 606 + -210 = 396
44x = 396

Divide each side by '44'.
x = 9

Simplifying
x = 9

See similar equations:

| 3(8x+31)+5(x+1)=u | | 2x+7=X+1 | | 2*7x+14+2x*15=606 | | 2x+14+2x*15=606 | | -10(x-2)= | | 6=9x-8x+3 | | -9x-6y+3= | | 18p-3+7p+31= | | (13+a)+13= | | 0.80x+0.55(80)=0.40(100) | | y-12y= | | 12=m+2 | | 5(6x+35)+7(x+1)=u | | -2y+10=-2(2y+3) | | x-4=-13 | | 16x^2+y^2-16y=0 | | r+10=15 | | 16x^2+y^2=16y | | -2+x=26 | | 2.1=x-6.1 | | (12)(6)6=x | | 3p=18 | | -10x=70 | | -7x=-168 | | -10.1x=30.3 | | 100(84)=96x | | -10x-20=-190 | | 4x+10x=56 | | 12z=-8 | | -11=x+4 | | 3x^2y+6x^2y^2-144xy^3= | | x^2-3x=-8 |

Equations solver categories